2017
DOI: 10.3892/ijmm.2017.2985
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of both ATF4 and PERK inhibits cell cycle progression and promotes the apoptosis of differentiating chondrocytes

Abstract: In the current study, we demonstrate that the silencing of protein kinase R (PKR)-like endoplasmic reticulum (ER) kinase (PERK) and activating transcription factor 6 (ATF4) (using small interfering RNA expression constructs) inhibits the chondrocyte cell cycle and proliferation in vitro and ex vivo. The silencing of PERK alone using siRNA against PERK (siPERK) led to arrest in the G1 phase, it decreased the number of cells in the S phase, and delayed progressoin to the G2-M phase. Co-transfection with siRNA ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Zhang et al clarify that the upregulation of PERK signaling alleviates apoptosis of skeletal muscle cells under high-stress conditions of hibernation [18]. In addition, data from other studies manifests that the silencing of PERK contributes to the apoptosis of chondrocytes and pancreatic β-cells [19,20]. Our results suggested that PERK overexpression markedly inhibited H/ R-induced NCMs apoptosis, which demonstrated the cellular protective roles of PERK.…”
Section: Discussionsupporting
confidence: 67%
“…Zhang et al clarify that the upregulation of PERK signaling alleviates apoptosis of skeletal muscle cells under high-stress conditions of hibernation [18]. In addition, data from other studies manifests that the silencing of PERK contributes to the apoptosis of chondrocytes and pancreatic β-cells [19,20]. Our results suggested that PERK overexpression markedly inhibited H/ R-induced NCMs apoptosis, which demonstrated the cellular protective roles of PERK.…”
Section: Discussionsupporting
confidence: 67%
“…To confirm the effects of ATG5, ATG7, siPERK and siNrf2 on chondrocyte. C28I2 cells were infected with Ad-ATG5 (MOI = 80), Ad-ATG7 (MOI = 100), siPERK (50 nmol) or siNrf2 (50 nmol) and Ad-GFP prior to culture 24 h [31, 32]. pcDNA3.1(−)-ATG5 and pcDNA3.1(−)-ATG7 were transfected into cells for 24 h by liposome 8000(Invitrogen) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…However, sustained stress changes the adaptive response to a prodeath response and ultimately, the phosphorylation status of eIF2α appears to codetermine the balance between prosurvival or prodeath signalling . This is accomplished by the above mentioned delayed feedback through which the interplay of GADD34, ATF4 and CHOP results in the activation of genes involved in cell death, cell‐cycle arrest and senescence (Fig. ).…”
Section: Er Stress Consequencesmentioning
confidence: 99%